An Analysis of Psychoactive Medications Initiated in the ICU but Continued Beyond Discharge: A Pilot Study of Stewardship. (December 2020) - Kovacic, Nicole Lynn; Gagnon, David J.; Riker, Richard R.; Wen, Sijin; Fraser, Gilles L.
Background: Psychoactive medications (PM) are frequently administered in the intensive care unit (ICU) to provide comfort. Interventions focused on preventing their continuation after the acute phase of illness are needed. Objective: To determine the frequency that patients with ICU-initiated PM are continued upon ICU and hospital discharge. Methods: This single-center, prospective, observational study assessed consecutive adult ICU patients who received scheduled PM. Frequency of PM continued at ICU and hospital discharge was recorded. The patient's primary treatment team was contacted by the pharmacist within 72 hours of ICU discharge to establish rationale for continued use or to suggest discontinuation. Results: Of the 60 patients included, 72% were continued on PM at ICU discharge and 30% at hospital discharge. The pharmacist contacted 40% of treatment teams after ICU discharge and intervention resulted in PM discontinued in 50% of patients. Post ICU discharge, the indication of 41% of patients' PM was unknown by the non-ICU care team or incorrect. Medical ICU patients or those transferred to an outside facility were more likely remain on PM at hospital discharge. Conclusion: PM are frequently continued during transitions of care and often without knowledge of the initial indication. Future studies should establish effective PM stewardship methods.